LncRNA-Fendrr protects against the ubiquitination and degradation of NLRC4 protein through HERC2 to regulate the pyroptosis of microglia - Li-Qing Wang; Yue-Ying Zheng; Heng-Jun Zhou; Xiong-Xin Zhang; Pin Wu; Sheng-Mei Zhu (BMC, 2021)
Abstract Objectives Targeted inhibition of inflammatory response can reduce diabetic cerebral ischemia-reperfusion (I/R) injure. Pyroptosis is characterized by caspase-1 dependence and the release of a large number of pro-inflammatory factors. LncRNA-Fendrr is associated with a variety of diseases, but Fendrr has not been studied in diabetic cerebral I/R. NLR-family CARD-containing protein 4 (NLRC4) regulate the pyroptosis of microglia cells. This study was designed to investigate whether Fendrr is involved in the effects of diabetic cerebral I/R injury. Methods The diabetic brain I/R model in mice was constructed. Mouse microglia cell line BV-2 cells were exposed to high glucose followed by hypoxia/reoxygenation (H/R). Fendrr and some pyroptosis-associated proteins were detected by qRT-PCR, western blot or ELISA. HE staining was used to detect pathological changes. Microglia pyroptosis was detected by TUNEL staining. RNA pull-down and RNA Immunoprecipitation were used to detect binding of Fendrr to HERC2 (E3 ubiquitin ligase), and CO-IP detected binding of HERC2 to NLRC4. The ubiquitination of NLRC4 was detected by ubiquitination experiments. Results Fendrr was significantly increased in the diabetic cerebral I/R model, and NLRC4 inflammatory complex and pyroptosis mediated inflammatory factors were increased. NLRC4 and inflammatory cytokines associated with pyroptosis were decreased in the high glucose-treated hypoxia/reoxygenation (H/R)-induced microglia after Fendrr knockdown. Fendrr bound to HERC2 protein, and HERC2 bound to NLRC4. Meanwhile, Fendrr could inhibit the ubiquitination of NLRC4, HERC2 promoted the ubiquitination of NLRC4 protein. Moreover, the effect of Fendrr overexpression in the diabetic cerebral I/R model of microglia can be reversed by HERC2 overexpression. Conclusion Fendrr can protect against the ubiquitination and degradation of NLRC4 protein through E3 ubiquitin ligase HERC2, thereby accelerating the pyroptosis of microglia.